EFEK SUMBER PUPUK ORGANIK DAN JUMLAH BENIH PER LUBANG TANAM TERHADAP ANALISIS PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays-saccharata Sturt) - Anak Agung Bagus Sugiarsana; Maria Theresia, Darini; Sri, Widata (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to determine the interaction between the source of organic fertilizer and the number of seeds per planting hole on the growth and yield analysis of sweet corn plants. The research was carried out from June to December 2022, located in Giwangan, Yogyakarta. This research was structured in a Complete Randomized Block Design (RAKL) with 4 factorial replications. The first factor is the source of organic fertilizer, namely the source of cow manure, chicken manure, compost. The second factor is the number of seeds, namely one per planting hole, and two per planting hole. The variables observed included leaf area, leaf area index, plant dry weight, plant growth rate, relative growth rate, ear weight per plant, ear weight per hectare, ear diameter, number of rows, and level of seed sweetness. Data analysis used variance at 5% level then continued with DMRT (Duncan's Multiple Range Test) at α=5% level. The research results showed that there was no interaction between the source of organic fertilizer and the number of seeds per planting hole on the growth and yield analysis of sweet corn plants. Sources of organic chicken fertilizer (K2) increase the weight of cobs per sweet corn plant, but do not increase the growth analysis of sweet corn plants. The number of one seed per planting hole increases the ear weight per plant. The number of two seeds per planting hole increases the cob weight per hectare. The source of organic fertilizer and the number of seeds per planting hole resulted in a higher cob weight per hectare than the control. Keywords: sweet corn, source of organic fertilizer, and number of seeds.